Interactive HPC and the LUNARC Desktop Environment - Lindemann, Jonas; Follin, Anders (SC24-W: Workshops of the International Conference for High Performance Computing, Networking, Storage and Analysis, 2024)
Since 2011, LUNARC has aimed to provide an interactive HPC environment for its resource users. Several different architectures have been used, but since 2013, we have been using a remote desktop environment based on Cendio's ThinLinc [1] combined with a custom backend framework, GfxLauncher [2], supporting hardware-accelerated graphics applications and Jupyter Notebooks [3] submitted to the backend cluster.